2004
DOI: 10.1158/0008-5472.can-03-3885
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Retroviral Tagging for Identification of Genes Involved in Initiation and Progression of Mouse Splenic Marginal Zone Lymphomas

Abstract: Human B-cell lymphomas are frequently associated with specific genetic changes caused by chromosomal translocations that activate protooncogenes. For lymphomas of mice expressing murine leukemia virus, mutagenic proviral insertions are thought to play a similar role. Here we report studies designed to determine whether specific retroviral integration sites might be associated with a specific subset of mouse B-cell lymphomas and if the genes associated with these sites are regularly altered in expression. We st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
2
57
2
1
Order By: Relevance
“…20,21 High-throughput retroviral tagging identified that SOX4 expression was elevated in Sox11 in B-cell neoplasms mouse splenic marginal zone lymphoma and associated with tumor progression. 22 In this study, we showed that the nuclear expression of sox11 is highly associated with mantle cell lymphoma among B-cell lymphomas. Homogeneous nuclear staining of sox11 was observed in 54 of 57 (95%) mantle cell lymphomas, including 52 of 53 (98%) classical and 2 of 4 variant mantle cell lymphomas.…”
Section: Discussionmentioning
confidence: 62%
“…20,21 High-throughput retroviral tagging identified that SOX4 expression was elevated in Sox11 in B-cell neoplasms mouse splenic marginal zone lymphoma and associated with tumor progression. 22 In this study, we showed that the nuclear expression of sox11 is highly associated with mantle cell lymphoma among B-cell lymphomas. Homogeneous nuclear staining of sox11 was observed in 54 of 57 (95%) mantle cell lymphomas, including 52 of 53 (98%) classical and 2 of 4 variant mantle cell lymphomas.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast to other studies using the MMLV or in the AKXD or BXH2 inbred mouse lines to accelerate pre-T and pre-B lymphomas or myeloid leukemias (Li et al, 1999;Hwang et al, 2002;Kim et al, 2003;Erkeland et al, 2004;Iwasaki et al, 2004;Shin et al, 2004), this approach exploited the preferential tropism of the mAIDS virus for mature B lymphocytes and successfully accelerated cancer progression in IgHm-HOX11 Tg mice. The relatively low number of integrations observed (B1.9 per tumor) is consistent with reports that the Du5H mAIDS virus yields fewer (between 2 and 4) integration events when compared to MMLV (between 6 and 10) or with other models of recombinant inbred mouse strains characterized by laterally transmitted retroviruses (Huang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral-derived DNA sequences that integrate adjacent to cellular oncogenes or within coding regions of tumor suppressors, can result in altered host gene expression contributing, ultimately, to clonal expansion of the infected cell. While the proviral tagging approach has resulted in the discovery of many genes involved in lymphoid and myeloid leukemias (Li et al, 1999;Hwang et al, 2002;Kim et al, 2003;Erkeland et al, 2004;Iwasaki et al, 2004;Shin et al, 2004), less work has been conducted on mature B-cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sox4 appears to have a dominant role in conferring oncogenic and metastatic transformation (Rhodes et al, 2004). High levels of Sox4 mRNA expression have been observed in a large number of human tumors including breast, lung, brain, prostate and ovarian cancer, and the Sox4 gene locus has been repeatedly found to be targeted by tumor-promoting retroviral integration in mice (Lund et al, 2002;Suzuki et al, 2002;Shin et al, 2004). Together, these studies support the inclusion of Sox4 as one of the 64 genes that constitute a general cancer signature (Rhodes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%